SYNTHESIS, CHARACTERIZATION AND SWELLING PROPERTIES OF POLY (ACRYLAMIDE-CL-CARBOXYMETHYLGUARGUM) HYDROGELS - A.P. GUPTA; SUDHIR G. WARKAR (International Journal of Pharma and Bio Sciences, 2015)
Hydrogel materials based on Polyacrylamide and Carboxymethylguargum (PAM-Cl-CMG) were synthesized using potassium persulphate as initiator and N,N’methylenebisacrylamide as cross linking agent while analyzing the effect of concentrations of crosslinker and carboxymethylguargum on swelling behavior of PAM-Cl-CMG hydrogel. To evaluate their structure-properties relationship, these were characterized by FTIR Spectroscopy, SEM, and DSC. Percent swelling was selected as a parameter for deciding the best hydrogel in each series of CMG concentration. The hydrogels showed appreciable swelling and the swelling exponent has been found to be in the range of 0.6 - 0.9, thus indicating non-fickian diffusion mechanism. These hydrogels were further studied for their swelling behavior as a function of temperature, pH, and electrolyte concentration. The results indicate that the percent swelling is directly proportional to the CMG concentration and inversely proportional to the concentration of crosslinker. The swelling behavior of synthesized hydrogels were found sensitive to swelling conditions such as temperature, pH, and [NaCl].